Pemberdayaan masyarakat pekebun dengan pengolahan terong menjadi barongko dan nugget di Kabupaten Pinrang - Irwan Irwan; Ja'faruddin Ja'faruddin (Seminar Nasional Pengabdian Kepada Masyarakat, 2019)
This Community Partnership Program (PKM) were held at Paladang village of Pinrang regency. The purposes of this activity are to increase farmers' knowledge and skills in entrepreneurship, in processing eggplant/ banana into various valued products, in making expense book tracker, and in managing finances and marketing of the business. Problems found in the community showed that they lack of knowledge about entrepreneurship, lack of knowledge and skills on how to process eggplant/ banana into varied products with higher economic value, and the lack of knowledge and skills in managing finances and marketing. The methods used in program were training, mentoring, discussion and counselling in collaboration between the team and farmer groups. This method is carried out for two groups. The first group consists of 6 people and 5 people belongs to the second group. Evaluation and monitoring are carried out periodically for 4 months. The results showed that 1) the participants show improvement in skills knowledge in terms of entrepreneurship; 2) the participants improved their ability and skills in producing various products from eggplant with good economic value; and 3) the participants able to produce eggplant barongko and eggplant nuggets.